2022
DOI: 10.3390/horticulturae8020136
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparative Analysis of Genes and MicroRNAs Involved in the Floral Transition of the Xinjiang Early-Flowering Walnut (Juglans regia L.)

Abstract: For tree crops, shortening the juvenile phase is a vital strategy to advance fruit bearing and enhance the breeding efficiency. Walnut (Juglans regia L.) seedlings usually take at least eight to 10 years to flower, but early-flowering (EF) types can flower one or two years after planting. In this study, RNA sequencing (RNA-Seq) and microRNA sequencing (miRNA-Seq) were used for a transcriptome-wide analysis of gene and miRNA expression in hybrids of the Xinjiang EF walnut variety ‘Xinwen 81’ and later-flowering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This is facilitated by the fact that each species within the genus Walnut has the same number of chromosomes, allowing for successful cross-pollination and fruit production. According to a recent study conducted by Jin et al [22], empirical evidence indicates that walnuts exhibiting early-fruiting characteristics have a very brief infancy phase, with some individual plants capable of flowering and producing fruit within 2-3 years of being sown. In contrast, late-fruiting walnut varieties take 8-10 years until they are able to yield fruit.…”
Section: Discussionmentioning
confidence: 99%
“…This is facilitated by the fact that each species within the genus Walnut has the same number of chromosomes, allowing for successful cross-pollination and fruit production. According to a recent study conducted by Jin et al [22], empirical evidence indicates that walnuts exhibiting early-fruiting characteristics have a very brief infancy phase, with some individual plants capable of flowering and producing fruit within 2-3 years of being sown. In contrast, late-fruiting walnut varieties take 8-10 years until they are able to yield fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual differentiation in plants has gradually become a popular area of academic research in recent years, but research into the mechanisms of sexual differentiation in heteromorphic plants is currently lacking in depth. miRNA are an important class of regulatory molecules in plants and play an important role in the process of plant sex differentiation [24]. Expression of miRNA and their regulated target genes signi cantly affects the development and transformation of plant sexual organs [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from walnut buds with the RNA Easy Fast Plant Tissue Kit (TIANGEN, Beijing, China) as previously described [12]. RNA concentration and purity were detected with a NanoDrop 2000 (Thermo Fisher Scientific, Waltham, MA, USA) and agarose gel electrophoresis.…”
Section: Rna Extractionmentioning
confidence: 99%
“…The main cultivated varieties are Xinjiang precocious thin-skinned varieties, which are abundant in the Xinjiang region [11][12][13]. A previous study from our lab revealed the genetic factors underlying floral transition in early-flowering walnut using RNA sequencing and microRNA sequencing [12]. In this brief report, we isolated the key floral transition gene FLC and measured its dynamic expression levels at multiple growth stages.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation